Ethnic-specific BRCA1/2 variation within Asia population: evidence from over 78 000 cancer and 40 000 non-cancer cases of Indian, Chinese, Korean and Japanese populations. Issue 11 (22nd September 2020) - Bhaskaran, Shanmuga Priya; Huang, Teng; Rajendran, Barani Kumar; Guo, Maoni; Luo, Jiangtao; Qin, Zixin; Zhao, Bojin; Chian, Jiasheng; Li, Suicheng; Wang, San Ming
Abstract : Background: Germline mutation in BRCA 1 and BRCA2 ( BRCA ) is genetic predisposition for breast and ovarian cancer. Identification of mutation carriers is a critical step to prevent and treat the cancer in the mutation carriers. Human BRCA variation has been well determined as ethnic-specific by studies in Ashkenazi Jewish, Polish and Icelandic populations in the 1990s. However, sufficient evidence is lacking to determine if ethnic-specific BRCA variation is also present in Asia population, which is the largest and the most diversified in modern humans. Our current study aims to investigate ethnic-specific BRCA variation in Asian population. Methods: We performed a comprehensive data mining to collect BRCA variation data in Indian, Chinese, Korean and Japanese populations derived from over 78 000 cancer and 40 000 non-cancer cases. We standardised all BRCA variation data following the international standard. We made a systematic comparison between the datasets including variant composition, variation spectrum, variant type, clinical class, founder mutation and high-frequent variants. Results: Our analysis showed that over half of the Asian BRCA variants were Asian-specific, and significant differences were present between the four Asia populations in each category analysed. Conclusion: Data from our study reveal that ethnic-specific BRCA variation is commonly present in Asia population as existing in non-Asian populations. Our study indicates that ethnicity should be an important factor to consider in prevention and treatment of BRCA mutation-related cancer in the Asia population. We recommend that the current BRCA variation databases should include ethnic variation information in order to function as true global BRCA references.